2021
DOI: 10.1080/09273948.2021.1954200
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvascular Alterations in Patients with Quiescent Posterior and Panuveitis Using Optical Coherence Tomography Angiography

Abstract: Purpose: To quantify retinochoroidal vascular parameters using swept-source optical coherence tomography (SS-OCTA) in quiescent posterior and panuveitis. Methods: In this cross-sectional study, subjects with quiescent posterior and panuveitis underwent fundus imaging using SS-OCTA (DRI Triton®, Topcon, Japan). The metrics calculated were fractal dimension (FD), foveal avascular zone (FAZ) area, retinal vascularity index (capillary density index-CDI), and choroidal vascularity index (CVI). Results:We included 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…OCTA can provide high-resolution images of individual vascular plexuses in different retinal layers in a noninvasive manner. Previous studies have shown that OCTA plays an important role in the diagnosis and treatment of uveitis [ 21 24 ]. OCTA appears to be particularly useful for a detailed evaluation of retinal nonperfusion as well as improvement of retinal ischemia after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…OCTA can provide high-resolution images of individual vascular plexuses in different retinal layers in a noninvasive manner. Previous studies have shown that OCTA plays an important role in the diagnosis and treatment of uveitis [ 21 24 ]. OCTA appears to be particularly useful for a detailed evaluation of retinal nonperfusion as well as improvement of retinal ischemia after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological process associated with uveitis includes inflammation, vascular leakage and occlusion, local ischemia, and release of cellular and inflammatory mediators that can potentially lead to cystoid macular edema (CME), epiretinal membrane formation, artery and vein occlusions, retinal and choroidal neovascularization, vitreous hemorrhage, tractional retinal detachment, cataract, glaucoma, and so on. [ 1 2 ]…”
Section: Introductionmentioning
confidence: 99%